A Quantitative Assessment on Ecological Compensation Based on Water Resources Value Accounting: A Case Study of Water Source Area of the Middle Route of South-To-North Water Transfer Project in China - Chen, Junfei; Wang, Qian; Li, Qian (Frontiers in Environmental Science, 2022)
As an economic means to adjust the contradiction between ecology and development, ecological compensation plays an important role in promoting the good operation of inter-basin water transfer projects and the sustainable development of regional economy. The accounting of ecological compensation is the key and difficult point of ecological compensation as well as the basis of ecological compensation policy and practice. Watershed ecological compensation based on water resources value accounting is an early exploration field of ecological compensation research, and water resources value calculation needs to consider both water quantity and water quality comprehensively. Taking the water source area of the Middle Route of South-to-North Water Transfer Project (SNWTP) as an example, this paper tries to establish the payment standard of watershed ecological compensation from the perspective of water resources value. The results show that: 1) The water resources value of the six core regions in water source area has shown an overall upward trend since 2000, and the northern regions have demonstrated higher value of water resources than the southern regions. 2) LSTM neural network model is used to forecast the value of water resources in the six regions from 2020 to 2022, and it is found that the value of water resources would increase in the next few years. 3) The compensation price of the six regions in the water source area is predicted in the range of 0.5-1.5 yuan/m3 from 2020 to 2022, and an upward trend in the ecological compensation amount is forecast. Based on the above conclusions, this paper puts forward suggestions to establish ecological compensation accounting system in line with the Middle Route water source area from the perspectives of ecological compensation legislation, allocation of ecological compensation amount and introduction of market mechanism.